ธุรกิจการเมืองในรัสเซียใหม่ - รมย์ ภิรมนตรี (ศูนย์รัสเซียศึกษาแห่งจุฬาลงกรณ์มหาวิทยาลัย, 2011)
This article provides information on business-oriented politics in New Russia. This line of politics arose out of the continuing dependence of certain state enterprises on the supervision and control of the related ministries. This dependence resulted in the state enterprise managers having to offer certain benefits to the ministerial administrators in exchange for the latter’s favours that would facilitate the operation of the enterprises. This is the origin of the patronage system and corruption in this country. Another aspect of business-oriented politics is the involvement of most political party leaders and leading business figures in this line of politics. This involvement party evolved from the former communist party organization in which they had been once influential. These people took the opportunity to take hold of large shares of corporations that came into existence as a result of the privatization of state enterprises, even though these corporations had originally been designed such that their management and workers would jointly own 49 per cent of the shares, with the state owning the remaining 51 per cent of the shares. Businessmen and high-ranking government officials used this economic base and their monopolistic power to quickly develop their businesses and transform themselves into world-class billionaires in a relatively short period of five years, that is, between 1992 and 1997. Initially, there were more than 10 people who each owned assets worth more than US$1 billion; in 2004 the number of such people rose to 27. Their somewhat dubious and dishonest business activities included speculations on exchange rates and prices of goods during economic difficulties and high inflation, seeking benefits from price differences in case of discount concession goods being exported at very high prices, and reaping profits from purchasing shares at very low prices from workers and people who were compelled to sell their assets because of their poverty.Later, various groups of Russian businesspeople joined in setting up their own political parties to protect their business interests. These parties include the All Russia Unity, the Party of Economic Freedom and the Party of Free Work, which were all established in 1993. These people attempted to gain increasing political influence and power in Russian politics during the Boris Yeltsin government that focused on shock-therapy reform. The measures they adopted for this purpose include lobbying, running in elections, supporting their own people to obtain seats in parliament, and providing support for political parties such as by subsidizing their media propaganda.The article also provides a graphic presentation showing the channels through which business interest groups have exerted their political influence in New Russia, and a table displaying the financial support given by corporations and businesspeople to the political parties during their election campaigns in 1999.